Genetic ablation of the TET family in retinal progenitor cells impairs photoreceptor development and leads to blindness - Galina Dvoriantchikova; Chloe Moulin; Michelle Fleishaker; Vania Almeida; Daniel Pelaez; Byron L. Lam; Dmitry Ivanov (Proceedings of the National Academy of Sciences, 2025)
The retina is responsible for converting light into electrical signals that, when transmitted to the brain, create the sensation of vision. The mammalian retina is epigenetically unique since the differentiation of retinal progenitor cells (RPCs) into retinal cells is accompanied by a decrease in DNA methylation in the promoters of many genes important for retinal development and function. However, the pathway responsible for DNA demethylation and its role in retinal development and function were unknown. We hypothesized that the Ten-Eleven Translocation (TET) family of dioxygenases plays a key role in this pathway. To this end, we knocked out the TET family in RPCs and characterized the TET-deficient and control retinas using various approaches including electron microscopy, electroretinogram tests, TUNEL, RNA-seq, WGBS, and 5hmC-Seal. We found that while the TET-dependent DNA demethylation pathway contributes to the development of many retinal cell types, it is the most significant contributor to rod and cone photoreceptor development and function. We found that genetic ablation of TET enzymes in RPCs prevents demethylation and the activity of genes essential for rod specification and for rod and cone maturation. Reduced activity of genes responsible for rod specification results in the TET-deficient retina being depleted of these neurons. Meanwhile, reduced activity of genes responsible for rod and cone maturation leads to the underdevelopment or complete absence of outer segments and synaptic termini in the TET-deficient photoreceptors, which results in loss of their function and leads to blindness. These function-deprived, underdeveloped photoreceptors die over time, leading to retinal dystrophy.